2017
DOI: 10.3390/ijerph14020203
|View full text |Cite
|
Sign up to set email alerts
|

Driver’s Cognitive Workload and Driving Performance under Traffic Sign Information Exposure in Complex Environments: A Case Study of the Highways in China

Abstract: Complex traffic situations and high driving workload are the leading contributing factors to traffic crashes. There is a strong correlation between driving performance and driving workload, such as visual workload from traffic signs on highway off-ramps. This study aimed to evaluate traffic safety by analyzing drivers’ behavior and performance under the cognitive workload in complex environment areas. First, the driving workload of drivers was tested based on traffic signs with different quantities of informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 38 publications
6
64
0
1
Order By: Relevance
“…These results have congruent validity with the study conducted by Lyu et al, 29 in which cognition time was used to measure workload, and the average cognition time of traffic signs with level 1-4 information significantly increased. From the perceived workload point of view, a higher workload reflected that the driver required more resources to accomplish the driving task.…”
Section: Associations Between Sign Information and Driving Workload Osupporting
confidence: 89%
“…These results have congruent validity with the study conducted by Lyu et al, 29 in which cognition time was used to measure workload, and the average cognition time of traffic signs with level 1-4 information significantly increased. From the perceived workload point of view, a higher workload reflected that the driver required more resources to accomplish the driving task.…”
Section: Associations Between Sign Information and Driving Workload Osupporting
confidence: 89%
“…A previous study found significant physiological differences between the genders and males who endorse an exaggerated male stereotype are more likely to engage in aggressive driving behaviors [42]. Women have a stronger sense of obligation to traffic laws and tend to obey those laws while men tend to overestimate their driving ability and underestimate the risks associated with traffic violations [43][44][45].…”
Section: Driver's Characteristicsmentioning
confidence: 96%
“…Put simply, if other people believe you to be a poor driver, then you probably are. Both driver fatigue and risk-taking were associated with driving in poor weather; driver fatigue, perhaps understandably also linked to motorway driving, driving in heavy traffic and in adverse weatherendeavours acknowledged as both mentally and physically taxing [38].…”
Section: Discussionmentioning
confidence: 99%